Customer Orientation and SME Performance in Indonesia: the Moderating Role of Market Environment - Dewi Lusiana; Fakhrul Anwar Zainol (School of Business, IPB University (SB-IPB), 2026)
Background: A strong customer orientation is often associated with improved business performance. Yet, studies examining its effectiveness in emerging market settings, particularly among SMEs, are relatively scarce and highly dependent on contextual conditions.Purpose: This study examines the effect of customer orientation on business performance among Indonesian SMEs and investigates whether market turbulence and competitive intensity moderate this relationship.Design/methodology/approach: This study employs a quantitative, cross-sectional survey design. Data were collected from 122 SMEs using a purposive sampling method, targeting business owners and senior managers. The study focuses on the footwear manufacturing sector in Cibaduyut, Indonesia. Hierarchical regression analysis was used to examine both the direct effect of customer orientation on business performance and the moderating effects of market turbulence and competitive intensity.Findings/Result: The results demonstrate a significant positive association between customer orientation and business performance. Market turbulence enhances this effect, whereas competitive intensity shows no significant moderating role. This suggests that customer orientation may serve as a basic strategic necessity rather than a source of differentiation in intensely competitive markets.Conclusion: Customer orientation serves as a strategic capability that enhances SME performance, especially in turbulent markets. However, its effectiveness is context dependent and may diminish under intense competition unless complemented by additional differentiating strategies such as innovation or customer engagement.Originality/value (State of the art): This study extends market orientation research by empirically examining the moderating role of market environment (competitive intensity and market turbulence) in the relationship between customer orientation and business performance within Indonesian SME footwear manufacturing sector. Unlike prior studies that primarily focus on direct effects of customer orientation, this study provides more specific evidence on how external environmental conditions shape the effectiveness of customer orientation in a developing- country. The findings offer a more precise understanding of when customer orientation is most effective, thereby contributing to the literature on strategic marketing capabilities under environmental uncertainty and resource constraints. Keywords: business performance, competitive intensity, customer orientation, Indonesia, market turbulence, SMEs